Future Teacher’s Professional Competence Enhancement by Education Research Activity Arrangement - Lyazzat, Umbetyarova; Kalieva, Elmira; Aigul, Dauletkulova; Alma, Aitbayeva; Moldir, Assyl; Zhanat, issenbayeva (International Journal of Psychosocial Rehabilitation, 2020)
In recent years, in line with the communicative competence approach, especially in the domestic and foreign science actively developed the problem of formation of professional competence "as a mandatory component of the competence of professional qualifications of the modern expert". The higher education system at the present stage of development of society is undergoing significant changes due to the change of the model of cultural and historical development. But whatever reforms are not passed in the education system, they end up anyway, closed on a particular title - school teacher. That teacher is the key figure in the practice of the major innovations. And for the successful introduction of various innovations into practice, for the implementation of the new conditions of its tasks the teacher should have the necessary level and professional competence and professionalism. Issues of professionalism and professional competence in the last decade have become the subject of attention of psychological science (E.A.Klimov, A.K.Markova, L.M.Mitina, Yu.P.Povarenkov, N.S.Pryazhnikov and etc.).